Comparison of mechanical properties of hydroxyapatite derived from different additive powders with conventional sintering / See Kwan Wern - See , Kwan Wern (2018)
Hydroxyapatite powder was prepared by wet chemical precipitation using eggshells derived CaO and H3PO4. The effects of calcination of temperature on the purity of CaO extracted from waste eggshells were investigated from 700°C to 1000°C. XRD results show the formation of pure CaO with highest purity achieved at 900°C. Hence, a calcination temperature of 900°C was chosen to produce CaO. The hydroxyapatite powder obtained after precipitation was milled together with 0.5% wt additive of Zinc Oxide, Magnesium Oxide, Aluminum Oxide and Titanium Oxide for evaluated the mechanical and physical properties. The sintering temperature for these samples ranged from 1050°C to 1350°C. It was perceived that at sintering temperature from 1050°C to 1250°C, all the additive doped HA samples demonstrated better hardness and fracture toughness than undoped HA. The maximum Vickers hardness was at 1250°C for all the additives, the fractures toughness showed better results at 1150°C. At a sintering temperature of 1350°C, the hardness and toughness decreased. This is suspected to be due to the decomposition of HA to its secondary phases (α-TCP and TTCP) and hence reducing its performance. Among all the sintering additive, aluminum oxide shows the best performance for hardness and fracture toughness. The hardness of Aluminum oxide (Al203) doped HA peaked at 1250°C (7.551GPa) and the fracture toughness of Al203 doped HA peaked at a maximum value (1.35 MPam1/2) when sintered at 1150°C.